2014
DOI: 10.1155/2014/836025
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Raft-Associated Akt Signaling in Hepatocellular Carcinoma

Abstract: Caveolin-1 and flotillin-1 are considered as markers of lipid rafts which can be regarded as sorting platforms for targeted transport of transmembrane proteins and are involved in fundamental cellular events such as signal transduction, cell adhesion, lipid/protein sorting, and human cancer. We addressed caveolin-1 and flotillin-1 expression in 90 human hepatocellular carcinoma (HCC) and adjacent noncancerous tissues (ANT) samples by SDS-PAGE and immunoblotting with specific antibodies. Significant caveolin-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…IHC on liver sections was done following a published protocol [ 56 ]. Whole body perfusion of anaesthetised animals was done using normal saline for 15 minutes, followed by 4% PFA, till full body twitching and clearance of the tissue was observed.…”
Section: Methodsmentioning
confidence: 99%
“…IHC on liver sections was done following a published protocol [ 56 ]. Whole body perfusion of anaesthetised animals was done using normal saline for 15 minutes, followed by 4% PFA, till full body twitching and clearance of the tissue was observed.…”
Section: Methodsmentioning
confidence: 99%
“…PI 3K phosphorylates phosphatidyl inositol and helps in attachment and activation of second messengers that control cellular activities and properties including proliferation, survival, and motility [ 36 , 37 ]. Akt is one of the secondary downstream messenger protein which gets activation upon phosphorylation [ 38 ]. Phosphorylation of Akt leads to inhibition of proapoptotic signal as well as increase in antiapoptotic molecule [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fragmentation analysis along with activity staining of SOD proves that crude ethyl acetate extract was efficient in killing cancer cells [ 41 ]. Earlier findings reported that decrease in Akt level and increase in SOD may be due to enhanced activity of PTEN tumor suppressor [ 38 ]. It can be assumed that the triggering factor is the degradation of NF κ -B which leads to the change in oxidative stress of MCF-7 cells upon treatment of extract [ 42 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hypoxia has been reported to rapidly increase cellular cholesterol levels, thereby influencing the composition, number, and size of lipid rafts (41). Lipid rafts function as organizing centers for the assembly of signaling molecules; their increased rigidity optimizes spatiotemporal interactions and compartmentalizes proteins involved in specific signaling tasks (42,43). Interestingly, both RTKs and GPCRs can localize to lipid rafts, which provide a platform that facilitates interactions between EGFR and GPCRs, therefore enhancing the efficiency of transactivation (44).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, both RTKs and GPCRs can localize to lipid rafts, which provide a platform that facilitates interactions between EGFR and GPCRs, therefore enhancing the efficiency of transactivation (44). Lipid rafts have also been identified as key plasma membrane microdomains for Src-EGFR functional interactions as well as PI3K/Akt activation (42,45). It is therefore conceivable that, under hypoxic conditions, the recruitment of LPA 1 , Src, and EGFR in lipid rafts facilitates their interactions and that results in prolonged Akt activation and invadopodia formation.…”
Section: Discussionmentioning
confidence: 99%